Analysis of metrics for scientific dissemination about marine invertebrates on Instagram - Gonçalves da Costa, Karla; Singulani de Brito, Gabriela (Guará Journal, 2025)
Due to the easy accessibility of audiences of different ages, virtual social media are excellent alternatives for making science public domain. Therefore, the objective of this work was to disseminate scientific content about marine invertebrates through the @nubem_ufes profile on Instagram, analyzing the metrics provided by the social network. Over the course of a year, there was a 68.5% increase in the number of followers and content was created and posted weekly. The post with the greatest reach was viewed by 9,425 people, even with only 538 followers at the time, demonstrating access of 17.5 times the number of followers on the profile.Publications in the format of reels or videos were accessed more than static images, especially when there was participation by a team member. It can also be observed that the publications reached an audience in addition to those in the profile area, despite the majority being from the environmental area. Thus, as it is an easily accessible platform for all age groups, locations and because it covers people from different areas, whether academic or not, we conclude that Instagramproved to be efficient in reaching a diverse audience.
Keywords: Social media; Engagement; Marine Ecology; Education